MOONLIGHTING AND JOB SATISFACTION: A COMPARATIVE STUDY OF ACADEMIC STAFF AND MEDICAL PRACTITIONERS IN SOUTHWEST NIGERIA - Iyabode Abisola, Adelugba (Journal of Allied Research in Management and Entrepreneurship (JARME), 2022)
This study examines the cumulative impacts of moonlighting on job commitment, retention, and satisfaction among Nigerian public servants, specifically focusing on academic staff and medical practitioners in Southwest Nigeria. Moonlighting, the practice of holding multiple jobs, has become increasingly common due to rising living costs and the need for job security. However, it can have negative effects on employees' primary job performance, including poor performance, absenteeism, weariness, and career conflict. Despite its prevalence, moonlighting has received limited attention in research, particularly in the Nigerian context.The study aims to fill this research gap by investigating the consequences of moonlighting on job dedication, retention, and satisfaction in the Nigerian public sector. By analyzing the experiences of academic staff and medical practitioners, the study seeks to provide insights into the impact of moonlighting on these important employee outcomes. The findings can inform the development of favorable employment regulations and create an enabling atmosphere that promotes job satisfaction and commitment.Drawing on existing literature and empirical evidence, the study addresses the need for comprehensive research on moonlighting in Nigeria. Previous studies have primarily focused on universities and farmers, neglecting the health sector. Therefore, this research expands the scope of investigation by examining the health sector and its unique challenges related to moonlighting. By exploring the effects of moonlighting on job commitment, retention, and satisfaction, the study aims to contribute to the body of knowledge on this topic. The study employs a mixed-methods approach, incorporating quantitative surveys and qualitative interviews to gather data from academic staff and medical practitioners in Southwest Nigeria. Through statistical analysis and thematic coding, the research examines the relationships between moonlighting and the dependent variables of job commitment, retention, and satisfaction. The findings of this study are expected to have implications for government policymakers, stakeholders, management, and employers in Nigeria. By understanding the impacts of moonlighting, the government can design effective employment regulations and create a work environment that promotes employee satisfaction and commitment. Ultimately, this can lead to improved retention rates and enhance productivity and profitability in the public sector